PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP MINAT BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPAS MATERI EKOSISTEM KELAS III SD NEGERI JAMBEYAN 03 - Musthofa, Arya; Mulyati, Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the significant effect of implementing the Discovery Learning model on third-grade students’ interest in learning the Ecosystem unit of the Integrated Science subject, as well as to analyze the extent of the increase in learning interest after the model was implemented. The study employed a quantitative approach using an ex-post facto research design. The research was conducted at SD Negeri Jambeyan 03, Sambirejo Subdistrict, Sragen Regency. Data collection was carried out through questionnaires, participatory observation, and documentation. The data were analyzed using statistical procedures to test the research hypotheses.